Exponential stability of periodic solution for stochastic neural networks involving multiple time-varying delays - Zhigang Zhou; Li Wan; Qunjiao Zhang; Hongbo Fu; Huizhen Li; Qinghua Zhou (AIMS Mathematics, 2024)
This paper discusses the exponential stability of periodic solutions for stochastic neural networks with multiple time-varying delays. For these networks, sufficient conditions in the linear matrix inequality forms are rare in the literature. We constructed an appropriate Lyapunov-Krasovskii functional to eliminate the items with multiple delays and establish some sufficient conditions in linear matrix inequality forms, to ensure exponential stability of the periodic solutions. Several examples are provided to demonstrate that our results are effective and less conservative than previous ones.